Dietary Alteration of Cysteine and Methionine Sensitizes Gliomas to Ferroptosis Inducing Agents and Radiation. (16th November 2020) - Upadhyayula, Pavan S; Higgins, Dominique; Dovas, Athanassios; Mela, Angeliki; Chaudhaury, Kunal; Mahajan, Aayushi; Humala, Nelson; Sudhakar, Tejaswi; Kinslow, Connor; Stockwell, Brent; Canoll, Peter D; Bruce, Jeffrey N
Abstract: INTRODUCTION: Ferroptosis is an iron dependent form of regulated cell death mediated by lipid peroxides, which has proven to be a promising avenue for cancer treatment. METHODS: In vitro assays were performed using glioma cell lines previously established by our laboratory. Cell viability was assessed using bioluminescence. Flow cytometry was used to determine changes in lipid peroxidation (BODIPY-C11) and reactive oxygen species (ROS) (H2DCFDA) in normal and CMD conditions. In vivo studies were performed using stereotactic orthotopic injections in syngeneic mice, fed control or CMD diet. Subsets were also treated with radiation to assess synergy by measuring tumor burden via bioluminescence and survival. RESULTS: Both murine and human glioma cell lines are sensitive to ferroptosis induction. CMD sensitized tumor cell lines to ferroptosis by RSL-3, and IKE, and reduced glutathione levels. Short-term CMD dramatically increased lipid peroxidation and ROS in response to ferroptosis inducers. CMD treatment also increased stereotypic transcriptional markers of ferroptosis in glioma cell lines. Ex-vivo organotypic slices taken from primary human glioma surgical specimen showed similar findings. Co-treatment with CMD and radiation showed synergistic cell death in glioma cell lines. This was accompanied by a synergistic increase in lipid peroxidation in the co-treatment group. In vivo, the CMD diet was well tolerated. Co-treatment with radiation significantly reduced tumor size and prolonged survival ( P = .0093). CONCLUSION: These data show that CMD synergizes with radiation treatment, and may be a promising therapy to improve the efficacy of radiation treatment in glioma.